UAV assisted wireless hotspot - Alam, Rozana (2021)
Fifth Generation (5G) promises to expand mobile networks to serve multiple devices with diversified traffic patterns whenever and wherever needed and connecting new industries with surpassed performance. For traffic offloading, wireless backhauling, swift service recovery after disasters, emergency response, rescue, and search, unmanned aerial vehicle (UAV) can play an essential role in complementing the operation of cellular network. Due to affordable prices, flexible operation, and extensive availability, UAV has recently received much research attention. Nevertheless, most of the existing research focusses on modelling and simulation. There is a lack of work carried on UAV hotspot experimental verification. Therefore, the main objective of this research is to develop a UAV hotspot to validate the theoretical concept. The approach has several notable merits on facilitating demand-based communication like covering sports, rescue management from disasters, and boosting resilience against faults. Primarily, simulation has been carried out for analysing the air-to-ground channel characteristics based on established air-to-ground channel model. The development of wireless hotspot has been carried out using a portable software-defined radio (SDR) and Open-Air Interface software. For real-time measurement of air-to-ground channel characteristics, a prototype of UAV WiFi access point has been created using Raspberry Pi and a USB WiFi adapter integrated with a small quadcopter drone. A comprehensive verification of the study is carried out by using the aerial WiFi hotspot at different altitudes in an open suburban tropical area. The aerial hotspot prototype demonstrates that for UAV altitude up to 40m, real-time communication coverage can be provided to the ground users.